PROFILE OF BRAIN INJURY PATIENTS WITH COVID-19 INFECTION AT DR. SOETOMO HOSPITAL SURABAYA FOR THE PERIOD 2020 TO 2022 - Darian Mulyana; Agus Turchan; Imam Subadi; Tedy Apriawan (Journal of Social Research, 2024)
In 2019, a previously unidentified coronavirus was named COVID-19. This virus can infect everyone without exception, including brain injury patients. Because this virus is relatively new, there have not been many studies examining the interaction of COVID-19 with brain injury. The purpose of this study was to examine the profile of brain injury patients with COVID-19 at Dr. Soetomo Hospital. Method This study was conducted with a descriptive observational method with a retrospective approach. The data taken came from the medical records of Dr. Soetomo Hospital. The results of 56 brain injury patients with COVID-19, the majority of whom were male, most of whom were in the age range of 40 – 59 years, mild brain injury cases were the most dominant, the average length of patient stay was 16.4 days and patient mortality was 30.4%.